2004
DOI: 10.1021/jp049648e
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Fluorescence of 3-Methylindole:  A Theoretical Study, Including H2O Interactions

Abstract: The paper presents a computational study of the ground and excited states of 3-methylindole. The ground-state geometry is optimized using the DFT B3LYP potential in conjunction with a 6-31+G(d) basis set. In addition the ground and first and second excited singlet states are optimized, for the first time, using the CASSCF method with an ANO−S basis set. The results are compared with experiment and with the experimental and theoretical literature data for the parent indole. The calculated excitations are in agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
(66 reference statements)
2
21
0
Order By: Relevance
“…This combined strategy, consisting of starting with a DFT-optimized structure and subsequently reoptimizing the crucial structure parameters at the CASPT2 level, has been successfully applied in other studies. [32,36,37] All calculations have been performed within the abelian C 2 point group symmetry. For all atoms, atomic natural orbital basis sets, specifically designed to include relativistic effects, have been used.…”
Section: Methodsmentioning
confidence: 99%
“…This combined strategy, consisting of starting with a DFT-optimized structure and subsequently reoptimizing the crucial structure parameters at the CASPT2 level, has been successfully applied in other studies. [32,36,37] All calculations have been performed within the abelian C 2 point group symmetry. For all atoms, atomic natural orbital basis sets, specifically designed to include relativistic effects, have been used.…”
Section: Methodsmentioning
confidence: 99%
“…The CASPT2 study on indole by SerranoAndrés and Roos indicated that upon relaxation the 1 L b remains the lowest excited state, and will be the emitting state, as is confirmed by matrix isolation spectroscopy [139]. For 3-methylindole, where the splitting between the states is lower, the CASPT2 results point out that the optimization which starts at the 1 L a Franck-Condon state induces a state crossing between with the 1 L b state [137]. Nonetheless also in this chromophore the lowest excited energy level is the relaxed 1 L b state, and the emission maximum is calculated at 4.02 eV.…”
Section: Qm Calculations Of the Emission Spectramentioning
confidence: 82%
“…These transitions are immediately followed by a Rydberg excitation from the HOMO to MO33. In Table 4 we present calculated and experimental transition energies both for indole [135] and its homologue 3-methylindole [137]. In the latter model system the excitations are slightly red-shifted and the separation between the radiative states is lower than in indole, making it an even better model of the actual tryptophan chromophore.…”
Section: Quantum Mechanics (Qm) Calculations Of the Absorption Spectramentioning
confidence: 99%
“…The humidity control was rigorous as the Trp photoluminescence (PL) is quite sensitive to moisture variations. Somers and Ceulemans [47] studied the conformational changes in the Trp molecule when hydrated with water. The Trp degradation kinetics is also altered as a function of the amount of moisture because photolytic processes are usually accelerated in water.…”
Section: Methodsmentioning
confidence: 99%